2009
DOI: 10.1111/j.1741-3729.2009.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Effects of Sibling Relationships Among African American Adolescents

Abstract: This study investigated associations between sibling relationships and adjustment among 179 African American adolescent siblings (controlling for family factors), and tested moderating effects of familism values and birth order. Two-level random intercept models revealed that familism values moderated sibling relationship-adjustment linkages, suggesting that youth who reported both strong familism values and harmonious sibling relationships showed the most positive outcomes. These effects were more consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
6
21
0
Order By: Relevance
“…This is inconsistent with some studies in which a stronger effect was found for internalizing than for externalizing problems (Stocker et al, 2002). However, it is consistent with other findings that showed that effects of family support (Branje et al, 2004) as well as effects of sibling and parental warmth and support (Soli et al, 2009) on adolescent externalizing versus internalizing problems were quite similar. Adolescents seem to be just as likely to act out as withdraw in response to hostility and lack of warmth in the parent-adolescent and sibling relationship.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This is inconsistent with some studies in which a stronger effect was found for internalizing than for externalizing problems (Stocker et al, 2002). However, it is consistent with other findings that showed that effects of family support (Branje et al, 2004) as well as effects of sibling and parental warmth and support (Soli et al, 2009) on adolescent externalizing versus internalizing problems were quite similar. Adolescents seem to be just as likely to act out as withdraw in response to hostility and lack of warmth in the parent-adolescent and sibling relationship.…”
Section: Discussionsupporting
confidence: 58%
“…If one compares the effect sizes in the studies that examined both positive and negative affective quality, negative affective quality often shows stronger effects on problem behavior than positive affective quality (Buysse, 1997;Muris, Meester, & van den Berg, 2003;Soli, McHale, & Feinberg, 2009;Stormshak, Bellanti, & Bierman, 1996). These findings are consistent with the "bad is stronger than good" principle, which has been empirically confirmed for many psychological and sociological concepts (Baumeister, Bratlavsky, Finkenauer, & Vohs, 2001).…”
supporting
confidence: 74%
“…Half of the studies assessing age found significant protective effects. Kam and Bámaca-Colbert (2013) only found supportive parenting to be protective among middle, not but early adolescents, Soli et al (2009) found that familism in the context of sibling relational aggression protected against depression among older but not younger siblings, and Davis (2002) found that peer support buffered against low maternal support only among older but not younger adolescents. These findings suggest that there are likely additional individual characteristics beyond age, such as ones discussed below, modulating the interaction between risk and protective mechanism.…”
Section: Age Differencesmentioning
confidence: 98%
“…Familism, defined as feelings of support and obligations, protected African American and Hispanic adolescents against depression in the context of community violence and sibling relational aggression (Kennedy and Ceballo 2013;Soli et al 2009). However, familism did not protect Mexican-Americans in the risk context of economic hardship, discrimination, acculturative stress, family stress, or family conflict (Delgado et al 2011;East and Weisner 2009;Umaña-Taylor et al 2011).…”
Section: Familismmentioning
confidence: 99%
See 1 more Smart Citation